Cultura, educação e tecnologias em debate - Volume 3 - Almeida, Fernando José de; Torrezan, Gustavo Henrique; Lima, Luciana Piazzon Barbosa; Catelli, Rosana Elisa (Centro de Pesquisa e Formação Sesc São Paulo, 2020)
55 p.